European household and business expectations during COVID-19: Towards a v-shaped recovery in confidence? - Gene Ambrocio (Bank of Finland, 2020)
Confidence dropped universally across countries and sectors during the height of the COVID-19 pandemic in Europe. Latest survey data suggest that confidence is on track for a v-shaped recovery. The swift implementation of stringent containment measures as well as economic stimulus policy measures, along with several other country characteristics, correlate well with both the drop and recovery of confidence across countries.
urn:nbn:fi:bof-202007292265
Keywords: D84; E65; I10; 330; Confidence; Covid-19; Survey expectations